Tapping Aonla (Emblica Officinalis Gaertn.) Fruits for Nutraceutical Beverages - Jain, S. K.; Singh, Jitendra; Chauhan, P. S. (Indian Forester, 2013)
In present paper it has been strived to deal all nutraceutical attributes of 'aonla' rendering it suitable for processing besides delineating scope for development of beverages there from. 'Aonla' had been under use for preparation of conventional processed products such as preserve, 'chyavanprash', candy, dehydrated shreds, pickle, etc. Being rich source of vitamin C and poly phenols, aonla has strong antioxidant activity and therefore getting popular in recent years as nutraceutical food. But the harsh processing treatments involved may sometimes cause significant loss in its nutritive and pharmacological properties. Hence, alternatively aonla is put to use in the development of juice and beverages. Since it is highly acidic and astringent in taste it has to be mixed with other fruit juices such as lime, ginger, etc. for preparation of RTS, squash and syrups. Similarly, aonla juice could be utilized to mix with other fruit juices for development of vitamin C rich fruit juice based beverages.